Diversity in Unity Perspectives from Psychology and Behavioral Sciences - Newcombe, Peter; P. Piercy, Fred; A. Ariyanto, Amarina; Muluk, Hamdi; Sri Hartati R. Suradijono; Kristi Poerwandari, E. (Taylor & Francis, 2018)
Psychology; Behavioral science; Perspectives